MAZ induces MYB expression during the exit from quiescence via the E2F site in the MYB promoter. Issue 17 (29th September 2017) - Álvaro-Blanco, Josué; Urso, Katia; Chiodo, Yuri; Martín-Cortázar, Carla; Kourani, Omar; Arco, Pablo Gómez-del; Rodríguez-Martínez, María; Calonge, Esther; Alcamí, José; Redondo, Juan Miguel; Iglesias, Teresa; Campanero, Miguel R.
Abstract: Most E2F-binding sites repress transcription through the recruitment of Retinoblastoma (RB) family members until the end of the G1 cell-cycle phase. Although the MYB promoter contains an E2F-binding site, its transcription is activated shortly after the exit from quiescence, before RB family members inactivation, by unknown mechanisms. We had previously uncovered a nuclear factor distinct from E2F, Myb-sp, whose DNA-binding site overlapped the E2F element and had hypothesized that this factor might overcome the transcriptional repression of MYB by E2F-RB family members. We have purified Myb-sp and discovered that Myc-associated zinc finger proteins (MAZ) are major components. We show that various MAZ isoforms are present in Myb-sp and activate transcription via the MYB- E2F element. Moreover, while forced RB or p130 expression repressed the activity of a luciferase reporter driven by the MYB- E2F element, co-expression of MAZ proteins not only reverted repression, but also activated transcription. Finally, we show that MAZ binds the MYB promoter in vivo, that its binding site is critical for MYB transactivation, and that MAZ knockdown inhibits MYB expression during the exit from quiescence. Together, these data indicate that MAZ is essential to bypass MYB promoter repression by RB family members and to induce MYB expression.